Analysis of the promoters involved in enterocin AS-48 expression. - Rubén Cebrián; Sonia Rodríguez-Ruano; Manuel Martínez-Bueno; Eva Valdivia; Mercedes Maqueda; Manuel Montalbán-López (PLoS ONE, 2014)
The enterocin AS-48 is the best characterized antibacterial circular protein in prokaryotes. It is a hydrophobic and cationic bacteriocin, which is ribosomally synthesized by enterococcal cells and post-translationally cyclized by a head-to-tail peptide bond. The production of and immunity towards AS-48 depend upon the coordinated expression of ten genes organized in two operons, as-48ABC (where genes encoding enzymes with processing, secretion, and immunity functions are adjacent to the structural as-48A gene) and as-48C1DD1EFGH. The current study describes the identification of the promoters involved in AS-48 expression. Seven putative promoters have been here amplified, and separately inserted into the promoter-probe vector pTLR1, to create transcriptional fusions with the mCherry gene used as a reporter. The activity of these promoter regions was assessed measuring the expression of the fluorescent mCherry protein using the constitutive pneumococcal promoter PX as a reference. Our results revealed that only three promoters PA, P2(2) and PD1 were recognized in Enterococcus faecalis, Lactococcus lactis and Escherichia coli, in the conditions tested. The maximal fluorescence was obtained with PX in all the strains, followed by the P2(2) promoter, which level of fluorescence was 2-fold compared to PA and 4-fold compared to PD1. Analysis of putative factors influencing the promoter activity in single and double transformants in E. faecalis JH2-2 demonstrated that, in general, a better expression was achieved in presence of pAM401-81. In addition, the P2(2) promoter could be regulated in a negative fashion by genes existing in the native pMB-2 plasmid other than those of the as-48 cluster, while the pH seems to affect differently the as-48 promoter expression.